Usability evaluation of the digital anger thermometer app - Mattson, Donald C (Health informatics journal, 2017)
The digital anger thermometer is a prototype for a mobile application (app) for use with adults in anger management treatment. The digital anger thermometer incorporates standards of software development in addition to anger management resources from the Substance Abuse and Mental Health Services Administration. The digital anger thermometer underwent a usability study conducted by five expert reviewers. The results indicate that it is easy to learn, efficient, and ergonomically sound. However, it does not offer support features or user-error tolerance. The digital anger thermometer prototype requires additional usability studies and comparative research in order for it to become an actual mental health app.